Family Caregivers’ Knowledge About Their Ill Relatives’ Mental Illness And Treatment: Perspectives From The Niger Delta Region Of Nigeria - Izibeloko O. Jack-Ide; Felicia E. Amegheme (Journal of Behavior Therapy And Mental Health, 2016)
Background: Many people with mental illness rely on family and friends for support and to help them in their activities of daily living. At all points in the care of ill relatives, caregivers need information to deal with the patient’s care and treatment demands. Methods: This was a descriptive study carried out in a Public owned mental health out-patient clinic. The study consisted of fifty participants, who voluntarily completed a questionnaire regarding their knowledge about their ill relatives’ mental illness and treatment. Results: Majority (62%) were female, and (28%) were parents (66%) has primary level education, (76%) had no knowledge about illness of relatives, (84%) did not know the diagnosis (76%) had poor knowledge of medication, and (84%) could not recognize the side effects of medication. Conclusion: The need for information and education of family caregivers about ill relatives’ mental illness, and the important role of medication regimen in the control of symptoms of the disorders. Education on medication and other treatment strategies should be tailored towards each family caregiver’s understanding and level of education.
Keywords: Family caregivers